THE EFFECT OF MAXIMUM PHYSICAL ACTIVITY AND MANGGONG BAMBOO (Gigantochloa manggong) LEAF EXTRACT ON CATALASE ACTIVITY IN LIVER ORGAN OF RATS (Rattus norvegicus) - Supriyatin, Supriyatin; Rahayu, Sri; Apriana, Ririn (Metamorfosa: Journal of Biological Sciences, 2017)
Gigantochloa manggong , one of endemic bamboo plant in Indonesia is suspected to have exogenous antioxidant potential. Exogenous antioxidant can help the activity of endogenous antioxidant in the body when overtraining occurs. Antioxidant can be measured by catalase enzymes activity. This study was carried out to determine the effect of maximum physical activity and leaf bamboo extract on catalase activity in liver organ of rats. This research used experimental method with completely randomized design (CRD). The test groups were the control rats (E 0 R 0 ), leaf extract induced rats (E 1 R 0 ), swimming activity treated rats (E 0 R 1 ) and leaf extract induced and swimming activity treated rats (E 1 R 1 ). Data were analyzed by the two-way ANOVA statistical test. Bamboo leaf extract non-toxic and leaf extract contained flavonoids, alkaloids, triterpenoids dan saponins. Catalase units in the control group is 1.00 unit/ml, the induced leaf extract group is 0.89 unit/ml, the maximum physical activity group is 0.78 unit/ml and the maximum physical activity treated and induced leaf extract group is 0.56 unit/ml. Based on statistical test, catalase activity has no effect (p>0,05) on rats. It was concluded that maximum physical activity could not reduce catalase activity. Manggong bamboo leaves extract could not increase catalase activity and there was no effect between maximum physical activity and manggong bamboo leaf extract on catalase activity in liver organ of rats.
Keywords: antioxidant, catalase, manggong bamboo, physical activity